Evaluation of stakeholders' preferences in urban redevelopment - Noor Amila binti Wan Abdullah Zawawi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2011)
The multicultural society in Malaysia is ingrained with the built up heritage of its early townships. Architectural details of traditional shophouses, which are the early urban settlements, are a rich mixture of Chinese, Indian, European and Malay cultures. The recent vintage of these built up heritages poses a threat to their existence. Rapid development and escalating market value increasingly replace these buildings with newer and higher-density structures. The current guidelines on redevelopment for traditional areas and buildings have been heavily biased on façade conservation, regardless of other aspects such as cultural merits. The rigidity of the guidelines, or lack of it as perceived by others, has resulted in conflicts and inconsistent redevelopment outcomes, not to mention inefficient implementation of development plans because the stakeholders, particularly the existing community, disagree with planned development for their areas. The aim of this research is to objectively evaluate stakeholders' preferences in redevelopment decisions for traditional area. The subjective elements of multiple stakeholders' different values and interests are explored using Multiple Criteria Analysis (MCA). MCA has been widely applied in various urban land use decision making as a structured approach to semi-structured decision problems. It is believed that the structured approach in MCA can be of a significant benefit towards a more constructive and transparent decision process. Eventually, it will lead to easier acceptance of development plans, thus more effective implementation of the plans. Using a relatively common MCA technique, the Analytical Hierarchy Process, stakeholders' preferences on a set of criteria for redevelopment decision are derived and compared. It is found that homogeneity does not necessarily exist within and in between homogeneous groups. This study indirectly contributes to discovering the potential of MCA evaluation to increase transparency in redevelopment decision making process.